Sexual images depicting children : the EU legal framework and online platforms’ policies - Chatzinikolaou, Argyro (2020)
Sexual(ised) images of children may often be posted or shared on social network sites or content sharing platforms. While such material may be the result of abuse or coercion, evidence shows that it may often be linked to contemporary forms of sexual exploration or intimate communication among underage peers. The aim of this paper is to explore the boundaries of the EU legal and policy framework regulating online platforms' liability for hosting or not removing such imagery. Discussing popular online platforms' policies against their imposed responsibility to contribute to the fight against illegal child sexual abuse material (CSAM) revealed a tendency of online intermediaries to restrict more than legally required from them. However justifiable the adoption of this 'better safe than sorry' approach might be, it sparks additional controversy in relation to children's agency. Navigating between the protection and freedom of children, when the issue at stake associates with elements such as gender, morality, and culture, inherently perplexes the performed balancing and cannot guarantee easy public policy or private industry solutions. However, in the absence of clear and sufficient policy guidelines,online platforms have no other choice but to shape their policies based on popular cultural norms, their business plan, and their understanding of how sensitive content should be dealt with